Scimitar sendromu: farklı klinik tablolar ve sonuçlar - Demir, Fadli; Demir, Halil Ibrahim; Yücel, İlker Kemal; Dedeoğlu, Reyhan; Erdem, Abdullah; Aydemir, Numan Ali; Çelebi, Ahmet (Bayçınar Tıbbi Yayıncılık, 2014)
Amaç: Bu çalışmada Scimitar sendromu tanısı konulmuş hastalar değerlendirildi.Çalışmaplanı:Çalışmaya Ocak 2003 - Aralık 2011 tarihleri arasında kliniğimizde Scimitar sendromu tanısı konulmuş ortalama ağırlıkları 16.7±21.8 kg olan, 12 hasta (8 kız, 4 erkek; ort. yaş 4.0±4.8 yıl; dağılım 1 ay - 16 yıl), alındı. Hastaların klinik bulguları, fizik muayene, telekardiyografi, ekokardiyografi, kalp kateterizasyonu ve cerahi bulguları ve izlem verileri geriye dönük olarak gözden geçirildi.Bul gu lar: On iki hastadan beşi (%42) infantil tip ve yedisi (%58) çocuk/erişkin tip Scimitar sendromu olarak değerlendirildi. İnfantil tipteki hastaların tümünde taşipne ve kalp yetersizliği bulguları varken, çocuk/erişkin tipteki hastaların birinde tekrarlayan alt solunum yolu enfeksiyonu öyküsü vardı. Ek kardiyak defektler hastaların yedisinde atriyal septal defekt, birinde aort koarktasyonu, ikisinde patent duktus arteriyozus ve birinde ventriküler septal defekt ile pulmoner atrezi idi. Bir hastada iki taraflı Scimitar sendromu vardı. İnfantil Scimitar sendromlu hastaların tümü şiddetli pulmoner hipertansiyonlu iken, çocuk/erişkin tipteki hastalardan biri hafif pulmoner hipertansiyonlu idi. Aortopulmoner kollateral arter saptanan dokuz hastadan altısında arter transkateter yolla kapatıldı. On hastaya (%83) cerrahi girişim uygulandı. İnfantil Scimitar sendromlu bir hasta ameliyat sonrası erken dönemde, ameliyat edilmeyen iki taraflı Scimitar sendromlu diğer bir hasta ise takipte akciğer enfeksiyonu nedeniyle kaybedildi.So nuç: Scimitar sendromu farklı klinik tablolarla seyredebilen nadir bir sendromdur. Çocuk/erişkin tip hastalığı olan hastalar sıklıkla asemptomatiktir; ancak tekrarlayan akciğer enfeksiyonları da izlenebilir. Aortopulmoner kollateral oklüzyon semptomatik iyileşme sağlayabilse de özellikle Scimitar veni tıkanmış ve ilave kardiyak anomalisi bulunan hastalarda cerrahi gerekir.

Background: This study aims to evaluate patients diagnosed with Scimitar syndrome. Methods: Twelve patients (8 girls, 4 boys; mean age: 4.0±4.8 years; range 1 month to 16 years) with a mean weight of 16.7±21.8 kg who were diagnosed with Scimitar syndrome in our clinic between January 2003 and December 2011 were included. Clinical findings of the patients, physical examination, telecardiography, echocardiography, cardiac catheterization, and surgical findings and follow-up data were retrospectively reviewed. Results: Of 12 patients, five (42%) were considered with infantile type and seven (58%) with child/adult type Scimitar syndrome. All patients of infantile type presented with tachypnea and cardiac failure findings, while one patient with child/adult type had a history of recurrent lower respiratory tract infection. Additional cardiac defects were atrial septal defect in seven, coarctation in one, patent ductus arteriosus in two, and ventricular septal defect with pulmonary atresia in one patient. Bilateral Scimitary syndrome was present in one patient. All infantile type patients had severe pulmonary hypertension, while only one of the child/adult type patients had mild pulmonary hypertension. Six of nine patients with aortopulmonary collateral artery underwent transcatheter closure of the artery. Surgery was performed in 10 patients (83%). One patient with infantile type in the early postoperative period and another patient with bilateral Scimitar syndrome who was not operated during follow-up died due to pulmonary infection. Conclusion: Scimitar syndrome is a rare syndrome which may present with different clinical presentations. Patients with child/ adult type disease are often asymptomatic, however, may present with recurrent pulmonary infections. Although aortopulmonary collateral occlusion may provide symptomatic relief, surgery is indicated in patients with obstructed Scimitar vein and additional cardiac anomalies, in particular.
Scimitar syndrome: different clinical presentations and results
Keywords: Ekokardiyografi; Pulmoner Hipertansiyon; Scimitar Sendromu; Echocardiography; Pulmonary Hypertension; Scimitar Syndrome